Symptomatic treatment of children with anti‐NMDAR encephalitis. (28th August 2015) - Mohammad, Shekeeb S; Jones, Hannah; Hong, Martin; Nosadini, Margherita; Sharpe, Cynthia; Pillai, Sekhar C; Brilot, Fabienne; Dale, Russell C
Abstract : Aim: We performed the first study on the perceived benefit and adverse effects of symptomatic management in children with anti‐ N ‐methyl‐d ‐aspartate receptor (NMDAR) encephalitis. Method: A retrospective chart review was undertaken at two tertiary paediatric hospitals in Australia and New Zealand. We included 27 children (12 males, 15 females; mean age at admission 7y 1mo) with anti‐NMDAR antibodies in serum or cerebrospinal fluid with a typical clinical syndrome. Results: Only two out of 27 patients were white, whereas 16 out of 27 patients were from the Pacific Islands/New Zealand Maori. The mean duration of admission was 69 days (10–224d) and 48% of patients (13/27) needed treatment in an intensive care setting. A mean of eight medications per patient was used for symptomatic management. Symptoms treated were agitation ( n =25), seizures ( n =24), movement disorders ( n =23), sleep disruption ( n =17), psychiatric symptoms ( n =10), and dysautonomia ( n =four). The medications used included five different benzodiazepines ( n =25), seven anticonvulsants ( n =25), eight sedatives and sleep medications ( n =23), five antipsychotics ( n =12), and five medications for movement disorders ( n =10). Sedative and sleep medications other than benzodiazepines were the most effective, with a mean benefit of 67.4% per medication and a mean adverse effect‐benefit ratio of 0.04 per medication. Antipsychotic drugs were used for a short duration (median 9d), and had the poorest mean benefit per medication of 35.4% and an adverse effect‐benefit ratio of 2.0 per medication. Interpretation: Long‐acting benzodiazepines, anticonvulsants, and clonidine can treat multiple symptoms. Patients with anti‐NMDAR encephalitis appear vulnerable to antipsychotic‐related adverse effects. Pacific Islanders appear to have a vulnerability to anti‐NMDAR encephalitis in our region. Abstract : This article is commented on by Gadian and Lim on pages325–326 of this issue.